A Case of Tuberculosis Spondylodiscitis With Paraspinal Abscess in a 2-Year-Old Child - Jeannette Lay Kuan Goh MBBS, MRCPCH; Chia Yin Chong MRCPCH, FRCPCH; Samuel Zhi Rui Lim MBBS; Kevin Boon Leong Lim BMedSci, BMBS, FRCS FRCS, FRCSEd, FAMS; Natalie Woon Hui Tan MBBS, MRCPCH (SAGE Publishing, 2018)
In this article, we report a case of tuberculosis spondylodiscitis in a 2-year-old child. Imaging of her spine showed a paraspinal abscess. The diagnosis of spinal tuberculosis remains difficult, and we discuss its salient features and current management within the pediatric population.